2003
DOI: 10.1007/s00424-003-1150-8
|View full text |Cite
|
Sign up to set email alerts
|

Cation channels, cell volume and the death of an erythrocyte

Abstract: Similar to a variety of nucleated cells, human erythrocytes activate a non-selective cation channel upon osmotic cell shrinkage. Further stimuli of channel activation include oxidative stress, energy depletion and extracellular removal of Cl-. The channel is permeable to Ca2+ and opening of the channel increases cytosolic [Ca2+]. Intriguing evidence points to a role of this channel in the elimination of erythrocytes by apoptosis. Ca2+ entering through the cation channel stimulates a scramblase, leading to brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 73 publications
3
44
0
Order By: Relevance
“…Furthermore, several reports indicate that the mechanisms of volume loss or AVD during apoptosis can occur independent of the cell nucleus and other organelles [33,34]. For example, in erythrocytes, the Ca 2+ ionophore ionomycin was shown to induce a cell death process analogous to apoptosis with cell shrinkage, cell membrane blebbing, and externalization of phosphatidylserine [34]. These studies suggest that AVD can be caspase-independent and independent of other intracellular organelles.…”
Section: Potassium As a Key Player In The Regulation Of Apoptosismentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, several reports indicate that the mechanisms of volume loss or AVD during apoptosis can occur independent of the cell nucleus and other organelles [33,34]. For example, in erythrocytes, the Ca 2+ ionophore ionomycin was shown to induce a cell death process analogous to apoptosis with cell shrinkage, cell membrane blebbing, and externalization of phosphatidylserine [34]. These studies suggest that AVD can be caspase-independent and independent of other intracellular organelles.…”
Section: Potassium As a Key Player In The Regulation Of Apoptosismentioning
confidence: 96%
“…Berg et al [32] suggested that upon apoptotic stimulation, AVD in mature erythrocytes devoid of caspase-9, Apaf-1, and cytochrome c resulted from the activation of calpain, not caspases. Furthermore, several reports indicate that the mechanisms of volume loss or AVD during apoptosis can occur independent of the cell nucleus and other organelles [33,34]. For example, in erythrocytes, the Ca 2+ ionophore ionomycin was shown to induce a cell death process analogous to apoptosis with cell shrinkage, cell membrane blebbing, and externalization of phosphatidylserine [34].…”
Section: Potassium As a Key Player In The Regulation Of Apoptosismentioning
confidence: 99%
“…Taurine release is also triggered during PCD (516), and erythrocytes from the taurine transporter knockout mouse are more resistant to apoptosis (513). This might be related to the fact that TauCl, which is the chlorinated product of taurine, causes PCD through direct damage to the mitochondria (454), i.e., net loss of taurine could result in a reduction in TauCl and thus a reduced risk for PCD.…”
Section: Role Of Ion and Taurine Loss In Pcdmentioning
confidence: 99%
“…In nucleated erythrocytes, experimental induction of apoptosis does not necessarily activate caspases and is not necessarily prevented by zVAD.fmk (Daugas et al, 2001). Mature, senescing erythrocytes undergo at least those aspects of an apoptotic program that mark them for clearance by phagocytes: increase in intracellular Ca 2 þ , leading to exposure of phosphatidylserine, loss of K þ i , and cell shrinkage (Lang et al, 2003a(Lang et al, , b, 2004; see also, Macho et al, 1997). This process is at least partially mimicked by hyperosmotic shock, which likewise leads to phosphatidylserine exposure.…”
Section: Erythrocytesmentioning
confidence: 99%
“…This process is at least partially mimicked by hyperosmotic shock, which likewise leads to phosphatidylserine exposure. In this case, both increase in intracellular ceramide and influx of Ca 2 þ participate (Lang et al, 2003a(Lang et al, , b, 2004. Bratosin et al have argued that at least a partial explanation for the conflicting data concerning mature erythrocytes resides in the activity of cysteine proteases other than caspases.…”
Section: Erythrocytesmentioning
confidence: 99%